Can We Talk of Empathy in Online Communication in Education and Business? - TRIFU, Alexandru (Anuarul Universitatii "Petre Andrei" din Iasi - Fascicula: Drept, Stiinte Economice, Stiinte Politice, 2021)
The development is not only from the economic point of view, but also from the human perspective. We used information and experiences in the field, corroborated with my own experience and with the pandemic and post-pandemic realities, in order to highlight that empathy is a very sensitive and necessary factor for the human development Thus, it’s about a psychological feature of someone, the power to train each and every person’s capabilities and skills to get profit, in the case of firms, or to achieve behavioral performance and standards in education. The conclusion is obvious: in online conditions of teaching and working, with a high level of stressors, the empathy mean of action is diminishing. The results indicate that the face-to-face students increased their knowledge of the subject material at a higher percentage than the online students. In businesses, the use of empathy is also beneficial for win-win strategies.